The position of international law on the non-peaceful use of outer space - Albedwawi, Salim Ali Abdulla Mohamed (2023)
Outer space, due to its international nature and significance for all of humanity, has been the subject of several international agreements and conventions. These legal instruments are intended to provide a legal framework for the peaceful exploration and use of outer space. However, these international agreements and conventions, such as the Outer Space Treaty (OST) (1967), The Liability Convention (1972), and The Moon Agreement (MA) (1984), are lagging behind in terms of providing legal framework pertaining to peaceful exploration and use of outer space. This study evaluates how international agreements and conventions address the use of outer space for non-peaceful activities. It explores the history of space exploration, its various applications, and its legal definitions and foundations. This study reviews the main legal texts regulating space activities and examines the United Arab Emirates' space laws. The study also assesses the legality of militarisation in outer space. The data was collected through the library-based approach. Several methods of data analysis, such as critical, analytical and content analysis, were employed in analysing the data. The thesis began with the proposition that outer space agreements and conventions need to be revised and improved to ensure the peaceful use of outer space and put an end to the militarisation and weaponisation of outer space. The study finds that the use of remote-sensing satellites may incite conflicts impacting national security and sovereignty. Current space treaties lack a clear definition of outer space and criteria to differentiate it from airspace. Claims of sovereignty over space regions by any state conflict with the principle of free use of outer space, as stated in the OST (1967). Furthermore, the MA (1984) is outdated, failing to thoroughly address military space issues and technological advancements in military capabilities. In the light of the above, the study recommends clarifying the definition of outer space and updating international treaties to reflect technological progress and prevent non-peaceful activities, thereby protecting all nations' interests.